2014
DOI: 10.1109/tgrs.2013.2275203
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Glacier Changes Using Multitemporal Multipolarization SAR Images

Abstract: This paper presents a processing chain for change detection of Arctic glaciers from multitemporal multipolarization synthetic aperture radar images. We produce terrain corrected multilook complex (MLC) covariance data by including the effects of topography on both geolocation and SAR radiometry as well as azimuth slope variations on polarization signature. An unsupervised contextual non-Gaussian clustering algorithm is employed for segmentation of each terrain corrected polarimetric SAR image and subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The highlighted part in the middle is the Nordenskjöld glacier (1), for which a slowdown along one longitudinal transect was exhibited in [25]. The map shows that this deceleration pattern also occurs in the northern part, close to the Sarqardliup sermia (3), and in the South in the area of the Polonia glacier (2). Notice that according to the color scale the end of the pattern is observed earlier in the middle-left part (mostly blue) than in the northern and southern parts (magenta).…”
Section: Qualitative Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The highlighted part in the middle is the Nordenskjöld glacier (1), for which a slowdown along one longitudinal transect was exhibited in [25]. The map shows that this deceleration pattern also occurs in the northern part, close to the Sarqardliup sermia (3), and in the South in the area of the Polonia glacier (2). Notice that according to the color scale the end of the pattern is observed earlier in the middle-left part (mostly blue) than in the northern and southern parts (magenta).…”
Section: Qualitative Resultsmentioning
confidence: 94%
“…Studying glacier dynamics is of primary interest to assess the local impact of climate change and derive their contribution to the sea level rise. One effective way to characterize glacier evolutions consists in analyzing Displacement Field Time Series (DFTS) obtained from Satellite Image Time Series (SITS) (e.g., [2,19,5,9]). When it comes to automatically gain insights into a DFTS, data mining techniques are to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Displacement Field Time Series (DFTS) analysis is an emerging research field fueled by the development of photogrammetry and remote sensing techniques, and by application needs of primary importance, such as landslide monitoring (e.g., [1,2]) or glacier dynamics analysis (e.g., [3][4][5][6]). Basically, a DFTS covers a geographical zone and gives the surface displacements observed between acquisitions performed at different dates.…”
Section: Introductionmentioning
confidence: 99%
“…The use of synthetic aperture radar (SAR) sensors is attractive in temporal studies, because SAR sensors do not suffer from the limitations of cloud cover and solar incidence, contrary to optical sensors. Many studies have demonstrated the potential of SAR images in change detection and time series analysis, e.g., [1]- [6]. This study is devoted to the multichannel polarimetric SAR (Pol-SAR) sensor, which potentially provides increased detection capability, as compared to single-polarization SAR [7].…”
Section: Introductionmentioning
confidence: 99%